Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1017/s1368980021004705
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a voluntary industry code for advertising food to children and young people: an analysis of New Zealand television data

Abstract: Objective: To evaluate the impact of the 2017 update to the voluntary Advertising Standards Authority (ASA) Code for Advertising Food on children and young people’s exposure to unhealthy food advertisements on New Zealand television. Design: Audience ratings data were analysed for New Zealand children and young people’s television viewing for eight random days prior to (June to August 2015) and following (October to December 2018) the code update, from 6.00am-midnight (864 hours). Food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Recent research on children's exposure to UFB marketing in media and settings in NZ have demonstrated significant exposure to unhealthy product and brand marketing on television [35,36], outdoor settings in school zones [37][38][39], through sports sponsorship [40] and as a ubiquitous presence as they go about their daily life [41]. Children in the latest KidsCam study were exposed to UFB marketing an average of 68 times a day across all settings, which was more than twice their exposure to healthier food marketing (average 26 times per day), and 10% of their total marketing exposure was on screens [42].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on children's exposure to UFB marketing in media and settings in NZ have demonstrated significant exposure to unhealthy product and brand marketing on television [35,36], outdoor settings in school zones [37][38][39], through sports sponsorship [40] and as a ubiquitous presence as they go about their daily life [41]. Children in the latest KidsCam study were exposed to UFB marketing an average of 68 times a day across all settings, which was more than twice their exposure to healthier food marketing (average 26 times per day), and 10% of their total marketing exposure was on screens [42].…”
Section: Introductionmentioning
confidence: 99%